Training for specialists in the inventory and cataloguing of historic-architectural and urban heritage, for its conservations and management : Aleppo and Istambul cards-catalogue - Polichetti, Maria Luisa (Roma : CA, 1995)
Convenio con la Universidad de "La Sapienza", Roma.
Keywords: PRESERVACION ARQUITECTONICA; PATRIMONIO URBANO; PATRIMONIO ARQUITECTONICO; RESTAURACION; RELEVAMIENTOS; PATRIMONIO CULTURAL; CATALOGACION; DOCUMENTACION; INVENTARIO